2018
DOI: 10.1186/s13052-018-0508-7
|View full text |Cite
|
Sign up to set email alerts
|

Media devices in pre-school children: the recommendations of the Italian pediatric society

Abstract: BackgroundYoung children are too often exposed to mobile devices (MD) and most of them had their own device. The adverse effects of a early and prolonged exposure to digital technology on pre-school children has been described by several studies.Aim of the study is to analyze the consequences of MD exposure in pre-school children.MethodsWe analyzed the documented effects of media exposure on children’s mental and physical health.ResultsAccording to recent studies, MD may interfere with learning, children devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
65
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(83 citation statements)
references
References 30 publications
2
65
0
5
Order By: Relevance
“…To the best of our knowledge, our study was the first to explore the sensitive period for the impact of screen exposure on myopia. Additionally, the American Academy of Pediatrics recommended that children under 18 months should avoid screen exposure [39], and both the Italian and the Canadian Pediatric Society have made the guideline that screen time for children younger than 2 years is not advocated [16,40]. Our finding, if adequately confirmed in further studies, could help to strengthen and improve these recommendations.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…To the best of our knowledge, our study was the first to explore the sensitive period for the impact of screen exposure on myopia. Additionally, the American Academy of Pediatrics recommended that children under 18 months should avoid screen exposure [39], and both the Italian and the Canadian Pediatric Society have made the guideline that screen time for children younger than 2 years is not advocated [16,40]. Our finding, if adequately confirmed in further studies, could help to strengthen and improve these recommendations.…”
Section: Discussionmentioning
confidence: 61%
“…Studies concerning screen exposure and myopia have been conducted worldwide such as in China, Japan, India, Ireland and Denmark with a focus on school-age children, which led to discrepant findings. A study involving primary and middle school students in six provinces of China showed children had a higher risk of myopia whose parents did not limit their offspring's screen time [25]; Siofra and colleagues reported that using screens >3 h per day was associated with a higher risk of myopia among schoolchildren in Ireland [26]; the North India Myopia Study found screen viewing was a significant risk factor for myopia progression amongst children aged 5 to 15 years [10]; and the Copenhagen Child Cohort 2000 Eye Study revealed that using screen devices >6 h/day, compared to screen device use <2 h/day, induced a roughly doubled risk of having myopia among [16][17] year-old adolescents [27]. Moreover, another two studies in older children aged 6 to 18 years in Qatar demonstrated a highly positive association between prolonged screen time (more than 3 h/day) and poor vision [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the investigation into the effects of sleep hygiene and ecology (143), which are heavily influenced by sociocultural phenomena, have slowly presented themselves across children and adolescents (6-18 years). With the introduction of technology at the forefront of childhood influence (144,145), pediatric sleep habits and consequently quality is slowly gaining traction where studies flagged here are acknowledging the underlying weight of sleep hygiene on sleep quality and sleep quantity. Although at present, these tools are still demanding attention for further psychometric validation.…”
Section: Discussionmentioning
confidence: 99%
“…Even more dramatic has been the great increase in the use of such devices by young and very young children. A nationally representative survey of the United States found that 68% of children under the age of 2 used screen-based devices during a typical day [7], and another recent survey from Italy showed that 80% of children aged 3 to 5 years used their parent's smartphone [9]. Excessive screen time is associated with poor sleep, obesity and psychological problems among school-aged children and thus generally considered to be detrimental to children's health [8].…”
Section: Introductionmentioning
confidence: 99%